AC/DC/AC Z-source inverter - Tan, Eugene Hong Xiang. (2010)
The main thrust in wind energy conversion system (WECS) is to maintain a constant voltage at the output in spite of variation in wind velocity from the wind turbine. The Z-source inverter has been identified to exhibit both voltage buck-and boost-capabilities in steady-state. It employs a unique impedance network included between the DC power source and converter circuit. The power conversion efficiency of Z-source inverter is appreciably improved because of the traditional three-stage conversion system, consisting of rectifier, boost chopper and inverter, replaced by a two stage conversion systems comprising of rectifier and Z-source inverter. All the traditional pulse width-modulation (PWM) schemes can be used to control the Z-source inverter. When the DC voltage is high enough to generate the desired ac output voltage, normal PWM (pulse width modulation) is used. While the DC voltage is not enough to directly generate a desired output voltage, a modified PWM with shoot-through zero states is employed to boost the voltage.